Comparative study between mass closure suturing technique and Hughes repair in emergency midline laparotomies - Mukesh Kumar P; Sathyaraj P; Jemin Bharath R; Ramprasath S; Renganathan M (Asian Journal of Medical Sciences, 2023)
Background: The most alarming post-operative consequences for patients and doctors are wound infection and dehiscence. Post-operative wound infection and dehiscence lengthen the hospital stay after surgery. Aims and Objectives: The present study examined the incidence of wound infection, wound dehiscence, duration of hospital stay, and burst abdomen between conventional and Hughes repair techniques of midline laparotomy wound closure. Materials and Methods: A 12-month prospective study was performed in the General Surgery Department at Government Rajaji Hospital in Madurai. In total, 80 patients, divided randomly into two groups of 40 each, received emergency midline laparotomies for various reasons. The primary outcome measures the infection incidence, wound dehiscence, and burst abdomen at the end of 10 days by the assessing surgeon. Results: In the study group, 30 (75%) were males, and females were 10 (25%). In the control group, males were 29 (72.5%), and females were 11 (27.5%). The mean age in the study and control groups was 42.4±11.927 and 41.7±13.607, respectively. There was a significant difference in surgery duration between groups. Most patients, i.e., 27 (67.5%) and 19 (47.5%), had wound infection and dehiscence in the control group, respectively. There was a significant difference in wound infection (P=0.025), wound dehiscence (P=0.002), duration of hospital stay (P<0.001), and burst abdomen (P=0.02) between groups. Conclusion: Hughes repair is associated with less incidence of wound infection, wound dehiscence, burst abdomen, and duration of hospital stay compared to patients whose abdomen was closed using the conventional continuous technique.